The mistake of 1931: A general equilibrium analysis - Gauti B. Eggertsson; Benjamin Pugsley (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
This paper studies a dynamic general equilibrium model with sticky prices and rational expectations in an environment of low interest rates and deflationary pressures. We show that small changes in the public's beliefs about the future inflation target of the government can lead to large swings in both inflation and output. This effect is much larger at low interest rates than under regular circumstances. This highlights the importance of effective communication policy at zero interest rates. We argue that confusing communications by the US Federal Reserve, the President of the United States, and key administration officials about future price objectives were responsible for the sharp recession in the US in 1937-38, one of the sharpest recessions in US economic history. Poor communication policy is the mistake of 1937. Before committing the mistake of 1937 the US policy makers faced economic conditions that are similar in some respect to those confronted by Japanese policy makers in the first half of 2006.
urn:nbn:de:hebis:30-38154
Keywords: E32; E52; E61; 330; Sticky Prices; Central Bank Communication; Stochastic General Equilibrium Model; Deflation; Geldpolitik; Zinspolitik; Konjunktur; Wirtschaftslage; Theorie